Generalized Dentin Dysplasia in a Four-Year-old dog. (June 2021) - Hutt, Jason P.; Volker, Mary Krakowski; Alterman, Jennifer B.; Soukup, Jason W.; Bell, Cynthia M.
Dentin dysplasia is an autosomal-dominant genetic abnormality that occurs in humans and results in diffuse radiographic dental abnormalities and variable tooth discoloration due to an underlying defect in secondary dentinogenesis. This case report presents distinctive radiographic and histopathologic dental abnormalities in a dog that are consistent with generalized dentin dysplasia. These findings are similar to but not completely analogous to any specific clinical type of dentin dysplasia in humans. Grossly, the majority of the teeth in this case were discolored and most were determined to be vital. Dentin dysplasia should be included in the list of differential diagnoses of discolored teeth and notably this form of discoloration does not necessarily indicate loss of vitality.